Lactobacillus reuteri DSM 17,938 ameliorates LPS-induced depression-like and anxiety-like behaviors by modulating gut microbiota and brain metabolic function - Xiaolong Mo; Siyi Guo; Dian He; Qisheng Cheng; Yichun Yang; Haiyang Wang; Yikun Ren; Lanxiang Liu; Peng Xie (Gut Pathogens)
Abstract Background Lactobacillus reuteri DSM 17,938 exhibits antidepressant and anxiolytic potential. The purpose of this study is to validate the effects of L. reuteri DSM 17,938 and preliminarily explore its underlying antidepressant and anxiolytic mechanisms, thereby providing a general direction for researching the targets of its antidepressant and anxiolytic effects. Methods The depressive mouse model induced by lipopolysaccharide (LPS) was intervened with L. reuteri DSM 17,938 (5 × 109 cfu/ml), and behavioral experiments were conducted to evaluate the therapeutic effects of the probiotic on depression. Moreover, the antidepressant and anxiolytic mechanism of probiotics was investigated through fecal metagenomics and fecal non-targeted metabolomics, as well as non-targeted metabolomics of the hippocampus and prefrontal cortex. Results In the behavioral experiments, L. reuteri DSM 17,938 significantly reversed the phenomena of reduced total moving distance, decreased center zone stay time and increased peripheral zone stay time in the open field test of LPS-induced depressed mice, and significantly reduced the immobility time of mice in the forced swimming test. L. reuteri DSM 17,938 restored gut microbial richness and ameliorated intestinal metabolic pathways in a depression mouse model, with lipopolysaccharide biosynthesis and ATP-binding cassette transporter (ABC) transporter metabolic pathways being significantly enriched. Untargeted metabolomics of the hippocampus and prefrontal cortex revealed that LPS intervention primarily induced dysregulation of amino acid metabolism-related pathways in these brain regions. In contrast, L. reuteri DSM 17,938 administration restored neural homeostasis, as evidenced by KEGG functional enrichment analysis identifying activated amino acid metabolism and unsaturated fatty acid metabolism pathways. Conclusion These findings collectively suggest that L. reuteri DSM 17,938 exerts antidepressant and anxiolytic effects by modulating gut microbiota composition to improve intestinal metabolism and subsequently rectifying amino acid and unsaturated fatty acid metabolic pathways in the hippocampus and prefrontal cortex. This study elucidate the gut-brain axis mechanisms underlying its antidepressant and anxiolytic effect and highlight its potential as a novel probiotic-based strategy for mood disorders.